Implementation Of The Traffic Safety Development Program By Dinas Perhubungan Surabaya" - Mayya Sobaroh; Kalvin Edo Wahyudi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Traffic safety is an important aspect that needs to be considered in order to reduce the number of accidents, especially among teenagers. This age group is among the most vulnerable to traffic accidents on the highway. One of the main factors in the high number of accidents in Surabaya is the lack of education and public awareness regarding road safety and traffic rules (Tukino et al., 2023). Therefore, various efforts need to be made to reduce the risk of accidents which continues to increase every year. As a form of prevention, the government through the Transportation Agency has designed a program that focuses on increasing traffic awareness, especially for junior high and elementary school students. The purpose of this study was to analyze the extent to which the implementation of the Traffic Safety Development program has been carried out. This study used a qualitative method with a descriptive approach, where data was collected through interviews and literature studies to gain a deeper understanding of the implementation of the program. The results of the study showed that this program had been implemented well and in accordance with the expected objectives. Based on the three main indicators in the success of a program, the Traffic Safety Development program obtained positive results in each indicator. This shows that the implementation of the program has been running effectively and has had an impact in accordance with the expected targets.  Keywords: Implementation, Safety, Traffic.